The Impact of Training and Development Programs on Employees Performance: The Case of Lebanese SMEs - Haidoura, Hani M (International Journal of Economics, Business and Management Studies, 2020)
Training is an agency’s effort to encourage training between its employees and development is an effort which is more focused on developing an employee’s abilities for potential responsibility. Professional development programs have implications for motivating and involving the employees in an attempt to improve performance. Training and development is an initiative by an organization to encourage the education of its staff, and learning is an emphasis on improving the future accountability capabilities of an employee. Training and development are a constant effort to improve workplace skills and organize productivity in order to improve workforce capability and output. In certain developed countries, such as Great Britain and the Economic Development of China, human capital training has played an important role. Such opportunities can also be found in a developing country such as Cameroon, with an abundant natural source of energy and financial support, if the development and mentoring of its human capital is given due consideration. Both components and activities in an entity involve human beings. For starters, managers would not be successful if a manager had subordinates who were not adequately prepared with experience, qualifications, abilities, and skills Some of the main objectives of human capital leadership is to create the conditions by which workers ’ latent ability will be noticed and their dedication to the organization’s achievement protected. The research implemented the quantitative methodology throughout distributing the questionnaires using the survey methodology and then analyzing the collected data using the SPSS statistical tool. The results showed a direct relationship between the mentioned variables since the regression analysis showed a relation below than 5%.